The educational experiences of Filipino youth in Quebec in the context of global migration - Caro, Josie Fely (Library and Archives Canada = Bibliothèque et Archives Canada, 2011)
Filipino youth in Montreal have one of the highest rates of not being in school. Reports of behavioural problems, difficulties integrating, school failure and parent-child relationship difficulties have been reported among Filipino Youth who came to Canada after their mothers came to work in Canada under the Live-In Caregiver Program and its predecessor, the Foreign Domestic Movement. Using a sociocultural framework, I interviewed seven Filipino youth to examine the factors that interact to influence their educational outcomes. I discovered that several of their problems were related to long periods of family separation. The inability to develop a close relationship with their mother, along with economic struggles was a source of difficulty and directly affected educational outcomes. The focus of learning French in order to do well in the Quebec High School system is another factor affecting the ability of Filipino youth to succeed in school.